Differences in biomechanics of abdominal wall closure with and without mesh reinforcement: A study in post mortem human specimens. (May 2020) - Le Ruyet, A.; Yurtkap, Y.; Hartog, F.P.J. den; Vegleur, A.; Turquier, F.; Lange, J.F.; Kleinrensink, G.J.
Abstract: Introduction: Small bites for the closure of the abdominal wall after midline laparotomy result in significantly less incisional hernias in comparison with large bites. However, fundamental knowledge of underlying biomechanical phenomena remains sparse. The objective of this study was to develop a digital image correlation-based method to compare different suturing techniques in terms of strain pattern after closure of a midline laparotomy in a passive model just after the time of surgery. Methods: A digital image correlation (DIC)-based method was used for the comparison of strain fields on the external surface of the myofascial abdominal wall (skin and subcutaneous fat removed) among six configurations, including an intact linea alba in five post mortem human specimens. The second configuration comprised primary mass closure with small bites (five mm between two consecutive stitches and five mm distance from the incision, 5x5 mm). The third configuration was primary mass closure with large bites (ten mm by ten mm, 10x10 mm). The fourth, fifth and sixth configuration comprised primary mass closure with large bites and the placement of a mesh in onlay position with two different overlaps and the use of glue to simulate the integration of the mesh within the soft tissue. Results: No visible difference was observed between 5x5 and 10x10 mm closure configurations. However, the use of mesh as suture line reinforcement highlighted a stiffer behavior of the midline area for similar intra-abdominal pressure, which was amplified when a larger mesh overlap was used. However, the whole abdominal wall showed quite similar shapes for the various configurations, except for the configuration with mesh reinforcement and the use of glue. Conclusion: Mesh reinforcement incited lower opening tension profiles in the midline area of the abdominal wall. following closure of the linea alba in median laparotomy. The next step should be to investigate the impact of mesh location ( e.g. retromuscular) and different time points after surgery. Graphical abstract: Image 1 Highlights: A high-potential DIC-based method was used for comparison in strain fields on the abdominal wall. No difference was observed between 5x5 and 10x10 for closure. The use of a mesh led to lower transverse strains along the midline.